Developing educational videos to inform rightly about school foodservice from kindergarten to high school: a case study - Gang, Gyoungok; Park, Chaewon; Kang, Haejin; Hong, Wan Soo; Park, Yoo Kyoung; Choi, Sook Hee; Kim, Seung Hye; Choi, Jieun; Park, Jihyun; Chang, Hyeja (Korean journal of community nutrition, 2024)
Abstract Objectives Since the enactment of the School Nutrition Act in 1981, school lunch programs in South Korea have grown quantitatively and qualitatively with a current student participation rate of 99.8%. Nonetheless, educational materials are needed to reduce misunderstanding and ignorance about school lunch programs. This study aimed to develop 3 educational videos that help students of various ages (kindergarteners/lower-grade elementary, upper-grade elementary, and secondary school, respectively), understand the school lunch program. Methods A scenario was created, was made, and the opinions on the scenario from experts in foodservice sectors were collected. A survey was conducted to students and parents to determine topics they wanted to know about school foodservice. The final videos were produced using this information and the expert opinions. The data were analyzed using SPSS 27.0 for Mac (IBM Corp., Armonk, NY, USA); a P-value of < 0.05 was considered significant. Results Three videos on school foodservice were developed for various age levels of students: kindergarten/lower-grade elementary, upper-grade elementary, and secondary school. Additionally, English subtitles were included for the multicultural student population. These videos, each lasting about 7 minutes, cover topics such as nutrition, hygiene, and the cultural significance of the school lunch program. The survey results showed that parents and students wanted to know the following topics about the school lunch program: “nutritionally balanced diet” (11.9%), “purchasing safe food ingredients” (10.9%), and “healthy eating habits” (9.9%). Conclusions The developed videos will serve as valuable educational resources on school foodservice, foster a deeper understanding of the school lunch program in parents and students, and potentially address their inquiries regarding production processes, nutrition, hygiene, cultural heritage, and health.